Pengaruh Model Pembelajaran Scramble terhadap Hasil Belajar Mata Pelajaran Seni Rupa Kelas III SD Inpres 2 Talise: The Influence of the Scramble Learning Model on the Learning Outcomes of Fine Arts Subjects in Grade III of SD Inpres 2 Talise - Shelyn Grasenia Podandi; Yun Ratna Lagandesa; Pahriadi Pahriadi; Muhammad Fasli; Kadek Hariana (ITScience (Information Technology and Science), 2026)
This study aims to determine the effect of the Scramble learning model on the learning outcomes in the fine arts subject for grade III SD Inpres 2 Talise. The learning outcomes of students in fine arts remain less than optimal and still need support to improve. This is due to learning that is still centered on the teacher and the lack of use of learning models that actively involve students. The research used is quantitative, employing the experimental method, while the design of this study is a One Group Pretest-Posttest Design. The sample for this study consisted of 19 grade III students at SD Inpres 2 Talise. Sampling used saturated sampling. Data collection techniques used were observation and learning outcome tests. The independent variable (X) in this study is the effect of the scrambled learning model, while the dependent variable (Y) is student learning outcomes. Hypothesis testing uses the paired sample t-test. The results of this study indicate that the average pretest score of 48.368 increased to 75.157 in the posttest after the application of the scrambled learning model. This is indicated by the t-test result of 0.000, which is smaller than 0.05 (0.000 < 0.05), so that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. These results indicate that the Scramble learning model can improve student learning outcomes in Fine Arts subjects. Thus, it can be concluded that the Scramble learning model influences the learning outcomes of grade III students at SD Inpres 2 Talise.